Influence of Green Accounting and Corporate Social Responsibility Disclosure on Firm Value with Profitability as an Intervening Variable - Fermadona, Hellen; Suryaningsih, Maria; Susilawati, Susi; Yuli , Rama (International Journal of Business, Law, and Education, 2025)
This study aims to examine the effect of green accounting and corporate social responsibility (CSR) disclosure on firm value, with profitability as a mediating variable. The research data were obtained from the annual reports of 35 energy sector companies listed on the IDX-IC index for the period 2019–2023, comprising a total of 175 observations. The data were analyzed using panel data regression and the Sobel test. The results showed that green accounting had no significant effect on profitability or firm value. CSR was found to have a significant effect on firm value but not on profitability. Profitability had a negative effect on firm value and was unable to mediate the effect of green accounting or CSR on firm value. This finding confirms that CSR implementation can improve market perception, but the internalization of green accounting and CSR has not been optimal in strengthening firm value. The implication of this research is the need for more integrated sustainability strategies for companies in the energy sector